Next step towards point-of-care molecular diagnosis of female genital schistosomiasis (FGS): evaluation of an instrument-free LAMP procedure - van Bergen, Kim J. M.; Brienen, Eric A.T.; Randrianasolo, Bodo S.; Ramarokoto, Charles E.; Leutscher, Peter; Kjetland, Eyrun F.; van Diepen, Angela; Dekker, Floris; Saggiomo, Vittorio; Velders, Aldrik H.; van Lieshout, Lisette (Frontiers in Parasitology, 2024)
Detection of Schistosoma spp. DNA in gynecological samples by quantitative real-time polymerase chain reaction (qPCR) is considered to be the reference diagnostic test for Female Genital Schistosomiasis (FGS). However, qPCR needs expensive laboratory procedures and highly trained technicians. Loop-mediated amplification (LAMP) is a more field-friendly isothermal procedure for the detection of parasite-specific DNA, but it still requires electrically powered equipment. Here, we validated a Schistosoma haematobium-specific Sh-LAMP procedure and tested a fully instrument-free isothermal amplification using a novel low-cost, and reusable Temperature-cup (T-cup) device. Specific primers were selected based on published assays, targeting the ribosomal intergenic spacer (IGS) region of S. haematobium. Technical validation of the IGS-Sh-LAMP was performed using 20 negative controls, including DNA extracts of soil-transmitted helminths and S. mansoni, and a 10-fold dilution series (100-10-3) of DNA extracted from a single S. haematobium egg (n=4). For clinical validation, the IGS-Sh-LAMP was tested on 125 DNA samples extracted from vaginal swabs of a previous FGS study in Madagascar. Results were compared with the quantification cycle value (Cq) of the standard ITS-2 targeting qPCR. Single S. haematobium egg DNA up to a 10-2 dilution and a ITS-2 Cq <35 tested positive in the IGS-Sh-LAMP. The specificity was found to be excellent (100%). In the clinical samples, IGS-Sh-LAMP showed comparable results with the qPCR, with 35.2% and 33.6% positives, respectively, and a concordance of 79.2% (99/125). Of the 12 false-negatives, 5 corresponded to the 7 qPCR positive samples with very low DNA levels (Cq ≥35). On the other hand, IGS-Sh-LAMP detected 14 additional cases that were not detected by qPCR. The T-cup IGS-Sh-LAMP performance was evaluated in a representative sub-selection (n=10) of IGS-Sh-LAMP positive clinical samples. The T-cup IGS-Sh-LAMP was found to be a very user-friendly method, but in different runs it missed 1 to 4 of the 10 IGS-Sh-LAMP positive samples, specifically those with a low DNA load. Our results show that the IGS-Sh-LAMP is a suitable alternative to the ITS-2 qPCR for the diagnosis of FGS in gynaecological samples, with high potential for the T-cup as a fully instrument-free isothermal amplification device for point-of-care diagnosis in low-resource settings.